2021
DOI: 10.1016/j.ajic.2021.01.005
|View full text |Cite|
|
Sign up to set email alerts
|

Surveillance testing reveals a significant proportion of hospitalized patients with SARS-CoV-2 are asymptomatic

Abstract: Background: The proportion of positive patients admitted to acute-care hospitals for reasons other than coronavirus disease-19 (COVID-19) is unknown. These patients potentially put other patients and healthcare workers at risk of infection. Objective: The objective of this study was to define the proportion of asymptomatic patients admitted with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). Secondary objectives were to define the positivity rate, reasons for admission, and the geographic distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Of these, 282 studies underwent full-text review. Ninety-five studies with information concerning the percentage of asymptomatic infections among the tested and confirmed populations were included in the final analysis 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 282 studies underwent full-text review. Ninety-five studies with information concerning the percentage of asymptomatic infections among the tested and confirmed populations were included in the final analysis 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , …”
Section: Resultsmentioning
confidence: 99%
“…Among 95 studies, 18 were excluded because that the percentage of asymptomatic infections among the confirmed population was 100%. 22 , 30 , 31 , 36 , 39 , 43 , 49 , 56 , 58 , 71 , 77 , 79 , 80 , 81 , 87 , 96 , 101 , 108 The remaining 77 studies were included in the meta-analysis for the percentage of asymptomatic infections among the confirmed population, 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 37 , 38 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 57 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 <...>…”
Section: Resultsmentioning
confidence: 99%
“…( Jin et al, 2020 , Haitao et al, 2020 ) A surveillance testing of hospitalized patients for SARS-CoV-2 from Louisville, Kentucky, USA found 76% of female gender among the asymptomatic cases. ( Arnold et al, 2021 )…”
Section: Discussionmentioning
confidence: 99%
“…This means patients are being infected while staying at the hospital. A surveillance study of hospitalized trauma and labor patients revealed a gradual increase in the rate of SARS-CoV-2 infection from 20% to 70% during their stay in the hospital ( Arnold et al, 2021 ). According to another study from Italy, the incidence of SARS-CoV-2 hospital-acquired infection is 12–15%.…”
Section: Discussionmentioning
confidence: 99%
“…2,33 SARS-CoV-2 breakthrough infections can occur in vaccinated HCP and patients making it still important to implement protocols that allow for detection of infectious individuals without relying on the presence of symptoms or contact tracing alone. Coupled with preventive measures such as PPE use, serial testing could help detect and prevent transmission within healthcare facilities in outbreak situations or with suspected nosocomial transmission.…”
mentioning
confidence: 99%